Ч . 1 : Введение в нефтегазовое дело; Нефтегазовое дело. Книга для студентов - Болсуновская Л. М. Людмила Михайловна; Абрамова Р. Н. Раиса Николаевна; Матвеенко И. А. Ирина Алексеевна; Терре Д. А. Дина Анатольевна (2015, 2015)
Заглавие с титульного экрана